Proposed Educational Policies and Structural Changes in Educational Development in Bangladesh - Ahmed, Rashed (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This article explores the proposed educational policies and structural changes in Bangladesh aimed at fostering inclusivity, quality, and innovation in education. By analyzing existing challenges and reform initiatives, the study provides a comprehensive understanding of the educational development landscape in Bangladesh. The study aims to identify key areas of reform in Bangladesh's education system, assess the feasibility and effectiveness of proposed policies, and highlight the challenges and opportunities associated with implementing these reforms. The research method is a literature review, which involves examining existing policies, reports, and academic papers on educational reforms in Bangladesh. The proposed educational policies and structural changes in Bangladesh reflect a comprehensive approach to addressing existing challenges and preparing for future demands. By focusing on inclusivity, quality, and innovation, these reforms have the potential to transform the educational landscape and contribute significantly to the country's socio-economic progress. Implementation challenges and offers insights into the potential impact of these reforms on achieving Sustainable Development Goal 4 (SDG 4).